1975
DOI: 10.1017/s0033291700056440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression on the speed of recall of pleasant and unpleasant experiences

Abstract: SynopsisAn experiment is described in which depressed patients were asked to recall pleasant or unpleasant experiences from their past life in response to a standard series of stimulus words. The ratio between the time for recall of pleasant and unpleasant experiences was found to fall progressively with increasing severity of depression or of ‘neuroticism’ and to be significantly related to each. Among patients who scored relatively low on depression or neuroticism pleasant memories were recalled more speedil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
148
1
2

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(170 citation statements)
references
References 12 publications
(19 reference statements)
19
148
1
2
Order By: Relevance
“…The present findings suggest that the representation of self in time seems to be independent of current mood, and therefore confirm and extend the results of previous studies on episodic memory (Lloyd & Lishman, 1975;Martin et al, 1983;Ruiz Caballero & Bermudez, 1995).…”
Section: Personality and Quality Of Mttsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings suggest that the representation of self in time seems to be independent of current mood, and therefore confirm and extend the results of previous studies on episodic memory (Lloyd & Lishman, 1975;Martin et al, 1983;Ruiz Caballero & Bermudez, 1995).…”
Section: Personality and Quality Of Mttsupporting
confidence: 92%
“…Moreover, the relationship between neuroticism and retrieval of episodic memories is constrained by reality, i.e., the actual events a person experiences, whereas as regards episodic future thinking, the effect of neuroticism might be more direct. It is also noteworthy to mention that, though some studies have shown that the effect of neuroticism on memory retrieval was affected by mood (Bradley & Mogg, 1994;Kuiper & MacDonald, 1982) while other studies did not (Lloyd & Lishman, 1975 ;Martin et al, 1983 ;Ruiz Caballero & Bermudez, 1995 ) and that the ability to generate future events was significantly altered by changes in mood (Hepburn, Barnhofer & Williams, 2006), the present finding show an impact of neuroticism on negative future thinking even when mood is controlled. Note.…”
Section: Personality and Mmt In Term Of Quantitycontrasting
confidence: 60%
“…Cognitive Effort, Memory, and Depressed Mood Memory deficits are well documented in clinically depressed patients (Badawi, 1985;Henry, Weingartner, & Murphy, 1973;Lloyd & Lishman, 1975;Russell & Beekhuis, 1976;Weingartner, Cohen, Murphy, Martello, & Gerdt, 1981) as well as in subjects who have been subjected to artificially induced depressed mood states (Bower, Gilligan, & Monteiro, 1981;Leight & Ellis, 1981). Why should depression impair memory?…”
Section: Cognitive Effort As a Boundary Conceptmentioning
confidence: 99%
“…É descrito que pacientes deprimidos teriam maior seletividade na evocação de material negativo [49][50] . Williams et al 51 sugerem que o processamento cognitivo ocorreria em dois tempos: um pré-atentivo (que segue a captura atentiva da informação e é refletido em testes de memória implícita) e outro elaborativo (que envolve a associação de informações-alvo com outras informações na memória, refletida em testes explícitos).…”
Section: Memóriaunclassified